ENHANCING INTENTION TO JOB APPLY THROUGH EMPLOYER ATTRACTIVENESS AND CSR: GEN-Z PERSPECTIVE - Septyawan, Arief Anom; Sumiati , Siti (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This primary objective of this study to determine the direct effect between employer attractiveness and corporate social responsibility (CSR) on intention to job apply. This study also aims to determine the indirect effect between employer attractiveness and CSR on intention to job apply mediated by corporate reputation variables. This study using quantitative research with non-probability sampling technique. The population of this research were generation Z fresh graduates in Semarang City. The sample in this study was 100 respondents. Data analysis in this study used SEM-PLS. This study found that the variables of employer attractiveness, CSR and corporate reputation have a direct effect on the intention to job apply. This study found that employer attractiveness and CSR have an indirect effect on intention to job apply mediated by corporate reputation.